Molecular genetic identification of viruses affecting pepper crop (Capsicum spp.) in Western North of Benin. - FANOU, André Antoine; MISSIHOUN, ANTOINE ABEL HOUMÈNOU; AGBANGLA, CLÉMENT (My University, 2019)
Chilli (Capsicum spp.) is a spice of economic importance and is widely cultivated for its fruits in Benin. Viral infestations are one of the major constraints that hamper agricultural production. The objective of the present work is to identify the viruses that affect off-season pepper cultivated in the Donga Department in north west Benin. All the communes of the Department were prospected and 16 fields were sampled. A total of 43 pepper accessions with leaves showing symptoms of virus diseases were collected. Six (6) phytovirus-specific primer pairs belonging to three botanical genera (Begomovirus, Tobamovirus and Potyvirus) were used for molecular identification. The results revealed the presence in the Department of Phytovirus of the genus Begomovirus present on 53.43% of the accessions, the genus Potyvirus present on 37.20% of the accessions and at last the genus Tobamovirus present on 6.97% of the accessions. The geographic distribution of the infestation remains globally high in all communes of the Department with 83.33% of the accessions in Copargo; 65.2% in Bassila, 53.83% in Djougou, and 75% in Ouaké. These results are significantly important for the definition of an improvement policy of off-season chilli production by setting up a program to control viral diseases.
Keywords: Capsicum spp. Chilli production Off-season crops Viral identification